2005
DOI: 10.1038/sj.npp.1300656
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Motivation Following Cocaine Self-Administration Under Extended Access Conditions: Effects of Sex and Ovarian Hormones

Abstract: We have previously shown that following extended access to cocaine, females, but not males, show marked increases in motivation to obtain cocaine, and we have hypothesized that such changes may contribute to long-term compulsive aspects of addiction that result in a persistent vulnerability to relapse. Here, we investigate the effects of extended cocaine access on short-term motivational changes in both male and female rats. An additional goal was to determine whether estrogen modulates motivation to self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 42 publications
9
48
1
Order By: Relevance
“…For example, when drug-naïve ovariectomized rats were given access to high unit doses of cocaine (1.0-2.5 mg/kg/ inj. ), acquisition of cocaine self-administration did not differ significantly from gonadally intact females (Caine et al, 2004;Grimm and See, 1997) or from ovariectomized females with estrogen replacement (Lynch and Taylor, 2005). Moreover, there were no differences in the shape and position of the cocaine dose-effect curve (0.032-3.2 mg/kg/ inj.)…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…For example, when drug-naïve ovariectomized rats were given access to high unit doses of cocaine (1.0-2.5 mg/kg/ inj. ), acquisition of cocaine self-administration did not differ significantly from gonadally intact females (Caine et al, 2004;Grimm and See, 1997) or from ovariectomized females with estrogen replacement (Lynch and Taylor, 2005). Moreover, there were no differences in the shape and position of the cocaine dose-effect curve (0.032-3.2 mg/kg/ inj.)…”
Section: Discussionmentioning
confidence: 73%
“…There were also no differences in the acquisition of cocaine self-administration (1.5 mg/kg/inj.) between ovariectomized females with and without estradiol replacement (Lynch and Taylor, 2005). Moreover, there were no differences in the shape and position of the cocaine self-administration dose-effect curve (0.032-3.2 mg/kg/inj.)…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…As the magnitude of active lever responding during reinstatement has been used as a measure of an animal's motivation to obtain cocaine (De Wit and Stewart, 1981;Self et al, 1996), another possibility is that activation of ERb by EB or DPN served to enhance the incentivemotivational state of the rat. Some support for this idea comes from one study that used a progressive ratio schedule of reinforcement to assess motivation and found that under certain conditions EB could enhance responding for cocaine under this schedule (Lynch and Taylor, 2005). However, more research is needed to specifically examine the effects of estrogen and the role of ERa and ERb on cocaineassociated motivational states.…”
Section: Possible Interpretations Of the Resultsmentioning
confidence: 99%
“…Female rats exhibit enhanced responding to psychostimulants in multiple paradigms in a manner both dependent and independent of ovarian sex hormones (Hu et al 2004;Jackson et al 2006). In ovariectomized rats, E 2 enhances the sensitization of cocaine-induced locomotor behavior and CPP (Segarra et al 2010), self-administration of cocaine on both fixed and progressive ratio schedules of reinforcement (Lynch and Taylor 2005;Zhao and Becker 2010), and preference for cocaine over food reinforcement in a discrete trials procedure (Kerstetter and Kippin 2011), and lowers thresholds for electrical brain stimulation of the ventral tegmental area (Galankin et al 2010). Thus, E 2 -enhanced expression of CPP could be interpreted as further evidence in females of "enhanced abuse liability to cocaine," yet this interpretation is at odds with the finding that E 2 also enhanced extinction of drug seeking.…”
Section: Discussionmentioning
confidence: 99%